The Effect of Anxiety on Pregnant Women during the Covid-19 Pandemic - Solichatin; Yefi Marliandiani (Program Studi S1 Kebidanan - Fakultas Sains dan Kesehatan Universitas PGRI Adi Buana Surabaya, 2021)
Pregnant mothers typically will experience both physical and psychological changes that naturally come alongside their physical and hormonal changes. The spread and transmission of SARS-CoV-2 is very rapid such that it is now considered as a pandemic. This pandemic force government to release several policies such as mask-mandate, handwashing-mandate, and crowd limitation to reduce the spread of the virus on everyone, including expecting mothers. Due to the pandemic, a lot of social interaction must be limited, including the routine pregnancy medical examination. In other hand, expecting mothers tends to be more easily anxious due to many reasons that can compromise their fetus and their own health. The objective of this research is to obtain a qualitative description of mothers’ anxiousness in relation to the COVID-19 pandemic situation. Google forms filled by the respondents were mainly used as tool to collect descriptive data in this research. The data was collected at Restu Pregnancy Clinic at Pakis Malang. 30 respondents who were doing ante-natal-care (ANC) are chosen by total sampling technique from the clinic. The data collected was then analyzed by frequency table and percentage. The instrument used was the perinatal anxiety screening scale (PASS). The result obtained indicated that most of the expecting mothers in the Restu Pregnancy Clinic are having light-medium level of anxiety level during COVID-19 pandemic situation.